CRITICAL DISCOURSE ANALYSIS OF KHOFIFAH INDAR PARAWANSA'S POSITIVE IMAGE IN NAJWA SHIHAB'S YOUTUBE VIDEO - Della Rizky Artanadya; Sufyanto (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study analyzes Khofifah Indar Parawansa in Najwa Shihab's YouTube video during the 2024 East Java regional elections. Using Teun A. van Dijk's critical discourse analysis theory, this study aims to determine how Khofifah builds her positive image in Najwa Shihab's YouTube video. Method: This study uses observation and documentation methods to collect the necessary data. Results: The results of the analysis show that Khofifah successfully built a positive image in the public eye through the use of polite and easy-to-understand language, as well as effective communication strategies on the YouTube platform. The main themes raised included strategies for surviving political contests and previous achievements, with an emphasis on good relations with political rivals and attention to gender equality issues. Novelty: Accordingly, through Van Dijk's critical discourse analysis, Khofifah has successfully built a positive image as a competent, inclusive, and visionary leader. This study is expected to contribute to political communication theory and provide insights for communication practitioners in building a positive image in digital media.